Hubungan Kondisi Ventilasi dan Pencahayaan Rumah terhadap Kejadian Tuberkulosis Paru di Wilayah Kerja Puskesmas Glugur Darat Tahun 2025 - Agnes Laurensia Gea; David Albert Pardede; Nathasia Simanjuntak; Putri Maria Regina; Athalia Famelinda Gracia Sinaga; Agnes Juni Jelita Sitohang; E. Tito Julianda Sinaga; Dina Octafrida Marpaung; Putri Chairani Eyanoer (Lembaga Pengembangan Kinerja Dosen, 2026)
Pulmonary Tuberculosis (TB) is a contagious infectious disease caused by the bacterium Mycobacterium tuberculosis through droplets from patients diagnosed with TB. Based on the Global TB Report 2024, WHO reported that Indonesia ranks second in the world, where 81% of cases were confirmed and 90% of them had received treatment, where there was an increase in the number of cases compared to 2023 with 77% of confirmed cases and 88% of them received treatment. The increase in the number of pulmonary TB cases is inseparable from factors that determine the transmission of M. tb such as the concentration of organisms in the air related to ventilation and the length of time a person inhales contaminated air. To determine the relationship between ventilation conditions and home lighting to the incidence of pulmonary TB in the working area of ​​the Glugur Darat Health Center in 2025 This study is an analytical study with a cross-sectional study design. Sample selection used the consecutive sampling method with 56 patients who met the inclusion criteria. Of the 56 people who met the criteria, 30 people (53.6%) were pulmonary TB sufferers and 26 people (46.4%) were not pulmonary TB sufferers. The majority of respondents were male (38 people) and the highest number was found in the 18-59 age range (48 people) (85.7%). Regarding ventilation conditions, 34 people (60.7%) did not meet adequate ventilation requirements, and 29 homes (51.8%) did not meet adequate lighting requirements. There was a relationship between ventilation conditions and the incidence of pulmonary tuberculosis in the Glugur Darat Community Health Center work area, but there was no relationship between home lighting and the incidence of pulmonary tuberculosis in the Glugur Darat Community Health Center work area.